DEATH OF WEB CITATIONS: A SERIOUS ALARM FOR AUTHORS - Tajeddini, Oranus; Azimi, Ali; Sadatmoosavi, Ali; Moghaddam, Hadi Sharif (Malaysian Journal of Library and Information Science, 2017)
The study explores availability and/or decay of URLs cited in articles of six Library and Information Sciences (LIS) journals published by Emerald, Science Direct and Sage. The research was performed using a descriptive survey method. Initially, all issues of the six journals including Information Processing & Management, Library & Information Science Research, Journal of Librarianship and Information Science, Journal of Information Science, Online Information Review, and Journal of Documentation from 2005 to 2008 were downloaded directly from their publisher websites. Afterwards, all the journals' citations in either print or Web formats were calculated manually. Then, availability and/or decay of individual cited URLs were examined in the Web environments. Two groups of URLs were identified as accessible (without any accessibility error) or inaccessible (with accessibility errors). Two groups of accessible URLs were â€œaccessible through first-checkâ€ and â€œaccessible through second checkâ€. Research findings indicated that 66% of articles had web citations. Original accessibility of web citations was 66% which improved to 95% by second check availability using the Wayback Machine and the Google. Overall, from 4562 cited URLs 34% had error messages mostly related to "File error" type. The study recommends that the best solution to prevent decay or disappearance of Web citations and diminish URLs decay is to check availability of citations from while they are being published. The Wayback Archive and the Google can revive the decayed citations.